Safety Awareness in Auto Mechanics Workshop Among Technical College Students in Lagos State - Ogunmilade Johnson O. (Matondang Journal, 2024)
The study investigated the safety awareness in auto-mechanics workshops among Technical College Students in Lagos State. The study adopted the survey type of descriptive research. The population of the study consists of eighty (80) technical college students in three technical colleges in Lagos state. Data were collected with the use of instrument namely: Safety Awareness in Auto Mechanics Workshop Questionnaires (SAAWQ). In the date processing the simple percentage and frequency counts were used to quantify and to analyse the responses. The result of the study showed that accidents prevention does not occur by itself, that it is the duty of the students, the teachers, instructors and administrators to be educated on why and how accidents happen. Also, the need to develop and adhere to safe working habits. Findings showed that using wrong tools to work, worn out tools, poor safety rules among others can cause accidents in the workshop. Based on the findings, it was recommended that the well planned workshop should be provided with standard facilities. Regular training and retraining program should be given for both teachers and students. Also, government must always visit the technical colleges and provide enough money for the school.